Using Econometrics to Understand Inclusion of Persons with Disabilities in the Workforce of Bosnia and Herzegovina - Ensar Sehic; Elma Satrovic; Seid Fijuljanin (Economic Review: Journal of Economics and Business, 2015)
Persons with disabilities have relevant working capacity. Employers who recruit those persons assume that their disabilities do not decrease organization's productivity. Persons with disabilities can normally fit into working environment. The studies of employers' attitude towards persons with disabilities are rare and of limited scope in Bosnia and Herzegovina (B&H). The aim of this multidisciplinary research is twofold: to investigate factors that may influence employment of persons with disabilities, and to examine employers' perceptions of persons with disabilities in terms of potential employment. The research team uses a sample of 101 employers from B&H and performs the logit model maximum likelihood estimation. The results show that the size of organization, in terms of the number of employees, primarily influences the likelihood of employment of persons with disabilities. There is an inverse relationship between employment opportunities and the organization size. One possible explanation for this relationship is that large companies already recruit persons with disabilities and therefore have no additional opportunities. Other coefficients in the estimated model are not statistically significant. The research also shows that employers in B&H have a positive attitude towards persons with disabilities, but they face issues that can be resolved by government incentives.
Keywords: C21; J23; J24; I12; I18; 330; employment policy; log-likelihood function; logit model; persons with disabilities